2015
DOI: 10.4238/2015.november.30.14
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum homocysteine level in the development of diabetic peripheral neuropathy

Abstract: ABSTRACT. The development of diabetic peripheral neuropathy (DPN) is always followed by changes in vascular endothelial cells that are related to the reactivity of the homocysteine (Hcy) sulfhydryl group. In this meta-analysis, we investigated the association of Hcy with the pathogenesis and progression of DPN. We screened the Embase, Ovid, PubMed, Web of Science, Wangfang, and China National Knowledge Infrastructure databases. All analyses were performed by using the STATA software, version 12.0 (StataCorp, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Kim et al reported that serum total bilirubin level was conversely linked with DPN [22]. Zheng et al showed that enhanced serum levels of homocysteine increased the risk of DPN development in patients [23]. Therefore, in the current study, we hypothesized that the serum NGF and BDNF levels would be beneficial to understanding the development mechanism and finding new therapeutic targets for DPN detection and treatment.…”
Section: Discussionmentioning
confidence: 89%
“…Kim et al reported that serum total bilirubin level was conversely linked with DPN [22]. Zheng et al showed that enhanced serum levels of homocysteine increased the risk of DPN development in patients [23]. Therefore, in the current study, we hypothesized that the serum NGF and BDNF levels would be beneficial to understanding the development mechanism and finding new therapeutic targets for DPN detection and treatment.…”
Section: Discussionmentioning
confidence: 89%
“…One study of 409 T2DM patients who underwent stress myocardial perfusion imaging showed that HCY levels were significantly associated with low levels of LVEF in the univariate analyses, and were independent of age, gender, smoking, blood pressure, renal function, folates, vitamin B12, lipid parameters, and hepatic enzymes (21). Other studies have shown increases in plasma HCY concentration in proliferative diabetic retinopathy, diabetic nephropathy, and diabetic peripheral neuropathy patients (22)(23)(24). Ala showed higher HCY levels in T2DM patients, and that HCY levels worsened with increased insulin resistance, dyslipidaemia, and poor glucose control (11).…”
Section: Discussionmentioning
confidence: 99%
“…While distal microcirculation of the hallux has been demonstrated to decrease in healthy subjects and those with Type 2 diabetes and intact skin, blood flow velocity on the dorsal foot significantly increased. This may have occurred due to differences in capillary density or due to a local "steal phenomenon" caused by vasodilation of the more proximal medium sized arterioles [35][36][37]. In subjects with a diabetic foot ulceration, distal hallux microcirculation increased after 14 sessions of one hour daily PEMF therapy performed over three-week timeframe.…”
Section: Discussionmentioning
confidence: 99%